Tunable Picosecond Optical Parametric Amplifiers for Time Resolved Resonance Raman Spectroscopy. Issue 1 (1999) - Towrie, M.; Gaborel, G.; Matousek, P.; Parker, A. W.; Shaikh, W.; Bisby, R. H.
Abstract : A picosecond optical parametric amplifier, OPA, system suitable for pump and probe spectroscopy has been developed. Two OPAs are simultaneously pumped by a titanium sapphire regenerative amplifier to produce several microjoules output over the 470 to 2000 nm wavelength range. One OPA used as the probe operates with c. 25 cm -1 linewidth over this tuning range. The system is optimised for TR 3 spectroscopy. Some preliminary experiments on Trolox, a water soluable Vitamin E derivative, are presented.